A atuação de Dom Daniel Hostin no processo de recatolização no Vale do Rio do Peixe - Rodrigues, Roberto Carlos (2020)
This dissertation aims to analyze how the “recatolization” process, a term given to the process of restoration and restructuration of the Catholic Church in Brazil, took place in the first half of the 20th century. Recatolization is the term used in this research to conceptualize the phenomenon in which Catholics who practice the so-called “popular Catholicism” are summoned to practice “Romanized Catholicism”, which sought to return to traditional Tridentine conservatism and, thereby, promoted the strengthening of the Catholic dogmas against the practices of “popular Catholicism” and doctrinal advances from other religious denominations. The focus of the work was on the performance of the first bishop of Lages, Dom Daniel Hostin, in the recatolization process, between the 1930s-1960s, at the region of the Lages’ Diocese - SC. Through various strategies, in common with a program of full alignment with the Universal Catholic Church, Dom Daniel, through close ties with various fields of society at western Santa Catarina and the Planalto Serrano region, sought to implant and reform the Catholic spirit. With this purpose, he implemented religious laws and practices, increasing and encouraging, above all, devotions to the Eucharist, nationalism, the Catholic hierarchy and the love and obedience to the Pope. The applied methodology was based on a bibliographic review concerning the theme, conducting documentary research in the minutes of visits and pastoral letters, bulletins and diocesan notices in the archives of the Diocese of Lages, and, above all, in the Tombo Book of the Parish of Joaçaba - SC, besides other official documents of the Catholic Church that contemplated Dom Daniel's performance in the proposed period. Newspapers and periodicals that address this issue were also consulted. The time frame from 1930 to 1960 was made necessary by the strong performance of Bishop Dom Daniel in the diocesan government in that period, which could be considered of paramount importance for the institutional advancement of the Catholic Church at the mesoregion West Santa Catarina. This work focuses on the relationship between Church and State, mainly in the imperial period; the power relations between the clergy and the local elites of the mesoregion West Santa Catarina and Planalto Serrano, in the period proposed by the research; the relationship of the ecclesiastical hierarchy with the lay faithful; the symbolic power proposed by Bourdieu; and the pendulum analogy, proposed by Ivan Manoel. This research intends to contribute to the discussion on the process of recatolization in the studied region, without exhausting the subject, serving as an instrument for future research on this topic.